Hoffman's Recalcitrant Dissecting Folliculitis - State of the Problem, Approach to Therapy, Demonstration of Clinical Cases - Marianna B. Drozhdina; Varvara A. Bobro (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
A review of the literature on the etiology, pathogenesis, and evidence base of therapeutic approaches for the management of patients with Hoffman's recalcitrant dissecting folliculitis is presented. The article describes the clinic of the disease, complications and optimal therapeutic tactics at the present stage. Attention is focused on the problem of antibiotic resistance and ways to solve it. A clinical case with a successful therapeutic outcome is presented. The article is illustrated with photos on the patients from the author's archive.